Seasonal Trends in Surface pCO2 and Air‐Sea CO2 Fluxes in Apalachicola Bay, Florida, From VIIRS Ocean Color. Issue 8 (21st August 2018) - Joshi, Ishan D.; Ward, Nicholas D.; D'Sa, Eurico J.; Osburn, Christopher L.; Bianchi, Thomas S.; Oviedo‐Vargas, Diana
Abstract: Estuaries have been recognized as important sources of carbon dioxide (CO2 ) to the atmosphere; however, contributions of these systems to regional and global carbon budgets are not well constrained due to limited information on seasonal and spatial variability. In this study, we use satellite remote sensing to obtain seasonal pCO2 distribution and air‐sea CO2 fluxes in Apalachicola Bay, a national estuarine research reserve located in the northern Gulf of Mexico that receives seasonally varying dissolved organic matter‐rich waters from the Apalachicola River. A combination of time series (2005–2016) and seasonal field observations (2015–2016) of pH and biophysical variables were used to develop seasonal pH‐pCO2 relationships for obtaining surface pCO2 estimates and air‐sea CO2 fluxes from Visible and Infrared Imaging Radiometer Suite (VIIRS) ocean color data. Monthly and seasonal maps of pCO2 and air‐sea CO2 fluxes showed a general trend of higher fluxes in winter and summer corresponding to high river flow and warm water temperatures. However, CO2 fixation via photosynthesis and low water temperatures contributed to lower fluxes to the atmosphere in spring and fall, respectively. Throughout the study period, Apalachicola Bay was a net source of CO2 with large seasonal and spatial variability and a mean annual CO2 flux to the atmosphere of 3.4 ± 3.1 mol·m −2 ·year −1 (9.4 ± 8.5 mmol·m −2 ·day −1 ), consistent with fluxes reported for other estuaries. This study demonstrates the critical role that satellite observations can play to improve the estuarine contributions to the global carbon flux estimates. Plain Language Summary: Despite having high productivity, coastal water bodies are known to emit large amounts of carbon dioxide (CO2 ) to the atmosphere. Our study demonstrates the use of an ocean color satellite to estimate seasonal and annual rates of CO2 release to the atmosphere in Apalachicola Bay, Florida (United States). Due to a lack of carbon dioxide measurements in Apalachicola Bay, we adopted a different approach with advanced statistical techniques to estimate CO2 concentrations from water acidity (pH). Our study shows that Apalachicola Bay is a net source of CO2 throughout the year; however, the rate of CO2 emission varies among months and seasons, and even in different regions within the bay—likely due to the dominance of one or more controlling processes. The estimated rate of emission in Apalachicola Bay indicates that it is a weak source of CO2, which has an annual CO2 emission rate ~95% lower than an average value for the subtropical estuaries around the world. This study also suggests that accurate CO2 flux estimates for Apalachicola Bay and other estuaries in the Gulf of Mexico fill an important gap in current global carbon emission estimates. Key Points: Seasonal and annual air‐sea CO2 fluxes were estimated using VIIRS ocean color imagery Apalachicola Bay (United States) is a net source of CO2 to the atmosphere that also experiences distinct monthly and seasonal variations corresponding to various biophysical processes Mean annual CO2 flux for Apalachicola Bay is 3.4 ± 3.1 mol·m −2 ·year −1